2014
DOI: 10.1111/psyp.12319
|View full text |Cite
|
Sign up to set email alerts
|

Focusing neurovisceral integration: Cognition, heart rate variability, and cerebral blood flow

Abstract: The neurovisceral integration hypothesis suggests in part that cerebral control of autonomic function conveys comparable control of executive function and, hence, correlation among vagally determined high frequency heart rate variability (HF-HRV), executive function, and regional cerebral blood flow (CBF). In 440 middle-aged men and women, resting HF-HRV was related to regional CBF derived from a resting arterial spin-labeled MRI scan and to seven neuropsychological tests of executive function. Despite some in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
83
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 99 publications
(91 citation statements)
references
References 55 publications
7
83
1
Order By: Relevance
“…However, it is consistent with a recent investigation of HRV and executive functioning using MIDUS II data (Kimhy et al, 2013), which likewise reported that significant relationships between a multifaceted EF factor and various HRV measures were reduced to nonsignificance by the addition of demographic covariates (age, sex, education). It is also consistent with a recent investigation of relationships between regional cerebral blood flow (rCBF), resting HF-HRV, and performance on a battery of seven EF measures (Jennings et al, 2014). This study reported significant associations between HRV and rCBF in several brain areas related to vagal control yet found no relationship of HRV to EF performance or to EF–rCBF associations.…”
Section: Discussionsupporting
confidence: 90%
“…However, it is consistent with a recent investigation of HRV and executive functioning using MIDUS II data (Kimhy et al, 2013), which likewise reported that significant relationships between a multifaceted EF factor and various HRV measures were reduced to nonsignificance by the addition of demographic covariates (age, sex, education). It is also consistent with a recent investigation of relationships between regional cerebral blood flow (rCBF), resting HF-HRV, and performance on a battery of seven EF measures (Jennings et al, 2014). This study reported significant associations between HRV and rCBF in several brain areas related to vagal control yet found no relationship of HRV to EF performance or to EF–rCBF associations.…”
Section: Discussionsupporting
confidence: 90%
“…We did not find any fasting-induced HF-HRV changes, which could explain the improved cognitive performance observed and its relationship with executive and nonexecutive fasting-induced changes (see Jennings et al [8] for review). In a previous study reported by Crippa et al [40], it was observed that the injection of acetylcholine into the prefrontal cortex of rats mediated a hypotensive response.…”
Section: Discussionmentioning
confidence: 62%
“…Recent years have shown growing interest in the association between autonomic cardiovascular function and the brain [8, 9] and in the observation that resting heart rate variability (HRV) as a marker of cardiovascular autonomic function [10] can reflect the activity of flexible and integrative neural networks allowing maximal organism accommodation in the face of rapidly changing environmental demands [9]. It has been suggested that there is a relationship between the vagally mediated high-frequency- (HF-) HRV and cognitive functioning (specifically with prefrontal-cortex-related tasks) [8] and between HF-HRV and mood [11, 12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One participant was missing depressive symptom scores. Although we have published neuroimaging findings from AHAB-II (Allen, Jennings, Gianaros, Thayer, & Manuck, 2015; Gianaros et al, 2014; Jennings, Allen, Gianaros, Thayer, & Manuck, 2015; Jennings et al, 2016; Marsland et al, 2015), the current findings are the first bearing on resting-state connectivity and inflammation in this sample.…”
Section: Methodsmentioning
confidence: 67%